Parents' Socioeconomic Status on Student Achievement - Triselvi Tita Atto; M. K. P. Abdi Keraf; Diana Aipipidely; Yeni Damayanti (Universitas Nusa Cendana, 2021)
Abstract The socioeconomic status of parents is a person's ability to meet all daily needs and school needs for children so that the children's school fulfillment can be fulfilled. The purpose of this study was to determine the effect of parents' socioeconomic status on the learning achievement of senior grade students at Manufui State Senior High School, Biboki Selatan District, North Central Timor Regency. This research is quantitative. The sample used in this study was the total sampling technique and the population taken in this study were all of the tenth-grade students at Manufui State Senior High School, South Biboki District, North Central Timor Regency with a total of 101 students. The data collection instruments were documentation of student achievement and a questionnaire on the socioeconomic status of parents. Hypothesis testing uses a simple linear regression test. The results showed that there was an influence between the socioeconomic status of parents on student achievement with a significant value of si (p) of 0.005 <0.05, with an R Square value of 12.6 %, while the rest was influenced by other factors.